2008
DOI: 10.1128/aac.01526-07
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility Profile of Streptococcus pseudopneumoniae Isolated from Sputum

Abstract: Streptococcus pseudopneumoniae is a recently described member of the Streptococcus mitis/oralis group of viridans streptococci that shares some characteristics with Streptococcus pneumoniae (1). Key characteristics of S. pseudopneumoniae are the absence of pneumococcal capsule, insolubility in bile, resistance or indeterminate susceptibility to optochin when incubated in 5% CO 2 but susceptibility to optochin when incubated in ambient air, and positive reactions in DNA probe hybridization and antigen detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
15
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 2 publications
4
15
1
Order By: Relevance
“…Among the latter, COPD, which was previously reported as a condition associated with S. pseudopneumoniae isolation, was rarely observed in this study (15 out of the 120 non-CF patients, including 5 patients with bronchitis and 7 with pneumonia) (4,6). We documented high rates of resistance to erythromycin and tetracycline, as previously reported (6,7). Of note, erythromycinresistant S. pseudopneumoniae isolates mainly exhibited an efflux phenotype, contrasting with the MLS resistance phenotype observed in 87.3% of the S. pneumoniae isolated in our institution during the study period.…”
supporting
confidence: 60%
“…Among the latter, COPD, which was previously reported as a condition associated with S. pseudopneumoniae isolation, was rarely observed in this study (15 out of the 120 non-CF patients, including 5 patients with bronchitis and 7 with pneumonia) (4,6). We documented high rates of resistance to erythromycin and tetracycline, as previously reported (6,7). Of note, erythromycinresistant S. pseudopneumoniae isolates mainly exhibited an efflux phenotype, contrasting with the MLS resistance phenotype observed in 87.3% of the S. pneumoniae isolated in our institution during the study period.…”
supporting
confidence: 60%
“…A great resistance rate of the studied S. pseudopneumoniae isolates was recorded for cotrimoxazole (75.0%), penicillin (62.5%) and erythromycin (56.2%) which was consistent with previous studies at which the same resistance pattern has been observed among studied isolates (Keith and Murdoch, 2008;Mohammadi and Dhanashree, 2012). Other studies have also documented a high resistance rate among S. pseudopneumoniae isolates to erythromycin (60%) without any recorded resistance to penicillin (Keith et al, 2006) that was in contrast with our finding and may be due to different antibiotic policy in other countries at which penicillin is used within limits.…”
Section: Discussionsupporting
confidence: 79%
“…While multilocus sequence analysis can reveal divergence between species by their housekeeping and virulence gene fragments (11,25), these methods are too cumbersome for large-scale and routine clinical diagnosis. Recent accounts of detection of pseudopneumococcus in carriage and symptomatic hosts with antibiotic resistance necessitate its accurate diagnosis as an emerging causative agent of disease (23). A recent report suggested that sequencing recA could differentiate between S. pneumoniae and S. pseudopneumoniae (43), but the study was performed with a smaller number of pseudopneumococcal strains solely from North America.…”
Section: Discussionmentioning
confidence: 96%
“…Virulence factors that were once thought to be exclusive to the pneumococcus, such as pneumolysin (encoded by ply) and autolysin A (encoded by lytA), have been detected in commensal streptococcal species (18,35,49), compromising their specificity as species identification markers. The pathogenic potential of S. pseudopneumoniae (the pseudopneumococcus) has been demonstrated in a murine model (12) as well as in humans (2,18,23,24,28,40). Rapid, correct identification of this organism in the clinical setting is essential for diagnosis and for understanding its disease potential.…”
mentioning
confidence: 99%